Asia-Pacific Fishing Livelihoods - Fabinyi, Michael (Springer Nature, 2022)
This open access book explores fishing livelihoods in the context of the wider contexts in which they are embedded. Drawing on case studies from across the Asia-Pacific region, the book highlights how fishing livelihoods are shaped by globalisation, social relationships and governance. The book concludes by showing how better understanding these relationships can contribute to governance for healthier ecosystems and social wellbeing. This is an open access book. This is an open access book.